Leaf Spraying of Manganese with Silicon Addition Is Agronomically Viable for Corn and Sorghum Plants - Oliveira, Kamilla Silva [UNESP] (2020)
Leaf spraying of manganese (Mn) is widely used in annual crops due to its deficiency in the soil. Silicon (Si) addition in the spray solution with Mn could favor physiological and nutritional aspects and the production of corn and sorghum plants. This study aimed to evaluate the effects of Mn and Si supplied by leaf spraying on leaf nutrition of corn and sorghum under Mn deficiency. Two experiments were carried out: one with corn and other with sorghum grown in pots filled with sand and using nutrient solution. Corn experiment consisted of a 4 × 2 factorial scheme, with Mn concentrations of 0.0, 0.29, 0.58, and 0.87 g L−1 in the absence and presence of Si (0.476 g L−1) applied on leaves at the V4 and V6 stages. The experiment with sorghum was carried out in a 4 × 2 factorial arrangement, with Mn concentrations of 0.0, 0.17, 0.34, and 0.51 g L−1 in the absence and presence of Si (0.476 g L−1) applied on leaves at the V4 and V6 stages. Physiological and dry mass production variables were evaluated in both experiments to verify the effect of Si and Mn on plant nutrition. Leaf spraying of Mn associated with Si increased micronutrient accumulation, relative chlorophyll index, quantum efficiency of PSII, and reflected on dry mass production of corn and sorghum plants. Leaf spraying of Mn associated with Si in the spray solution is agronomically viable for corn and sorghum plants.